The molecular mechanisms of cuproptosis and its relevance to atherosclerosis - Jiankang Wang; Zhian Chen; Hang Shang; Jiajuan Guo (Biomolecules & Biomedicine)
Atherosclerosis is a chronic inflammatory disease associated with lipid deposition in the vascular intima. Copper is a vital trace element implicated in the onset and progression of atherosclerosis. Excessive intracellular copper accumulation induces a unique form of cell  death termed “cuproptosis.” The emergence of the concept of cuproptosis has highlighted the potential role of copper in atherosclerosis. This review explores the regulatory mechanisms of copper metabolism and cuproptosis, summarizes recent findings on the link between copper excess and atherosclerosis, and examines how cuproptosis may influence atherosclerosis progression. The goal is to propose novel diagnostic and therapeutic strategies for atherosclerosis through the lens of cuproptosis.